Probiotics and health claims - Kneifel, Wolfgang; Salminen, Seppo (Chichester, West Sussex : Wiley-Blackwell, 2011)
This book examines the international picture regarding probiotic food applications, placing a particular emphasis on the legal context and assessment procedures of probiotic health claims in the major markets for these products. Health claim legislation is described and the ways in which manufacturers can ensure compliance are discussed. The book also covers the use of meta-analysis to assess available data, and case examples from various regulatory cultures and traditions are included. It will be of interest to food industry scientists, executives and R & D personnel; international regulatory a.
Probiotics and Health: From History to Future / Barry R Goldin -- The World's Oldest Probiotic: Perspectives for Health Claims / Tomoyuki Sako -- Probiotics: From Strain to Product / Arthur C Ouwehand, Lisbeth Sondberg Svendsen, Gregory Leyer -- Probiotics and Health Claims: Challenges for Tailoring their Efficacy / Christophe Chassard, Franck Grattepanche, Christophe Lacroix -- Probiotics: From Origin to Labeling from a European and Brazilian Perspective / Celia Lucia Ferreira, Marcos Magalhaes, Miguel Gueimonde, Seppo Salminen -- Substantiating Health Benefit Claims for Probiotics in the United States / Mary Ellen Sanders -- Health Claims and Dietary Guidance in the United States: Case 'Reduced Cardiovascular Disease Risk' / Alice H Lichtenstein -- Probiotics and Health Claims: A Japanese Perspective / Fang He, Yoshimi Benno -- Regulation of Probiotics in China / Anu Lahteenmski-Uutela -- Probiotics and Health Claims: An Indian Perspective / Jashbhai B Prajapati, Nagendra P Shah -- The Role of Meta-Analysis in the Evaluation of Clinical Trials on Probiotics / Hania Szajewska -- Applied Studies with Probiotics: Fundamentals for Meeting the Health Claims / Hannu Mykknen, Silvia W Gratz, Hani El-Nezami -- Probiotics Research: The Pediatric Perspective / Karl Zwiauer -- Probiotics and Health Claims Related to OTC Products and Pharmaceutical Preparations / Frank M Unger, Helmut Viernstein -- Probiotics and Health Claims: the Perspective of the Feed Industry / Anja Meieregger, Elisabeth Mayrhuber, Hans Peter Lettner -- Developing LGGʼExtra, a Probiotic Multispecies Combination / Maija Saxelin, Eveliina Myllyluoma, Riitta Korpela -- Probiotics and Health Claims: How to be Met by SMEs? / Miguel Gueimonde, Sampo J Lahtinen -- Probiotic Products: How can they Meet the Requirements? / Wolfgang Kneifel -- Probiotics and Health Claims: Hurdles for New Applications? / Lorenzo Morelli -- Probiotics and Innovation / Jean-Michel Antoine, Jean-Michel Faurie, Raish Oozeer, Johan van Hylckama Vlieg, Jan Knol, Herwig Bachmann, Jool Dore.
Includes bibliographical references and index.
Print version record.
Keywords: Probiotics -- Health aspects; Probiotics -- Law and legislation; Probiotics -- therapeutic use; Food Industry -- legislation & jurisprudence; Chemical engineering; Engineering; MEDICAL -- Pharmacology; Electronic books